Comparison of intravenous lignocaine versus combination of lignocaine with diltiazem on attenuation of haemodynamic responses to tracheal extubation in patients undergoing abdominal surgeries under general anaesthesia: A randomized double blind interventi - Kanchan Chauhan; Vivek Gupta; Sunil Chauhan; Manoj Soni (Journal of Applied Pharmaceutical Research, 2022)
Background: Tracheal intubation is frequently associated with cardiovascular stress response characterized by hypertension, tachycardia and increased serum concentration of catecholamines and similar phenomenon is also seen during extubation. During Endotracheal extubation increase in sympathoadrenergic activity is caused by epipharyngeal and laryngopharyngeal stimulation. Objective: The aim and objectives of this study are to compare the effect of combination of intravenous (i.v.) diltiazem 0.1 mg/kg and i.v lignocaine 1.0 mg/kg vs intravenous lignocaine alone to attenuate haemodynamic extubation responses and airway reflexes during extubation. Material and method: This study was undertaken with 72 patients belonging to the age group 20–60 years with physical status ASA Classes I and II of either sex. Group A received injection diltiazem 0.1 mg/kg and lignocaine 1 mg/kg. Group B received injection lignocaine 1 mg/kg with normal saline. In this study, the drug dosage was fixed based on the previous studies. Result: The baseline values of heart rate,systolic blood pressure (SBP), diastolic blood pressure (DBP) and mean arterial pressure (MAP) were statistically comparable between the two groups. The heart rate, SBP, DBP, and MAP was significantly high in group A (lignocaine) as compared to group B (diltiazem with lignocaine) at extubation and till 1 min, 3 min, 5 min, and 10 min post extubation (pvalue<0.05). Conclusion: Combined diltiazem and lignocaine provides more effective prophylaxis than lignocaine alone for attenuating the cardiovascular responses to tracheal extubation